2018
DOI: 10.1108/bfj-01-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

How to best promote my product? Comparing the effectiveness of sensory, functional and symbolic advertising content in food marketing

Abstract: Purpose Advertising is one of the most important components of food marketing. However, there is uncertainty over the optimal means of convincing consumers to buy a product. The purpose of this paper is to examine the effectiveness of advertising content comprising text (sensory, functional and symbolic messages) and pictures (product image) on food product evaluation. Design/methodology/approach Two online experiments investigating strawberry advertisements were performed. Study 1 incorporated only text, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 75 publications
(92 reference statements)
3
12
0
Order By: Relevance
“…sensory appeal and perception of product design) provides additional evidence supporting the importance of product appearance. Additionally, these findings extend the current literature on sensory product perception (Haase and Wiedmann, 2018; Krishna et al , 2017) and product design research (Candi et al , 2017; Haase et al , 2018) by combining these factors in the specific case of industrial products.…”
Section: Discussionsupporting
confidence: 74%
“…sensory appeal and perception of product design) provides additional evidence supporting the importance of product appearance. Additionally, these findings extend the current literature on sensory product perception (Haase and Wiedmann, 2018; Krishna et al , 2017) and product design research (Candi et al , 2017; Haase et al , 2018) by combining these factors in the specific case of industrial products.…”
Section: Discussionsupporting
confidence: 74%
“…Effective marketing communication for organic food is also critical in the promotion of more sustainable behavior [94,95] since advertising and communications play such significant roles in determining food product consumption [96]. Also as acknowledged by other studies [97,98] effective integrated multi-media public awareness campaigns offer strong potential for promoting organic food consumption, particularly when used in conjunction with appropriate packaging information and trustworthy certification.…”
Section: Discussion and Practical Implicationsmentioning
confidence: 96%
“…Marketing communication for organic food consumption is a very important topic and need to be taken into account for promoting an SFC behaviour. Advertising and communication, in general, play a very significant role in the evaluation of food products [157]. In terms of augmenting the sales of organic food through marketing and communication programs, relevant research has demonstrated that individuals consume more organic food when the benefits are already known to them [158].…”
Section: Conclusion-implementationmentioning
confidence: 99%
“…Within that context, Beltran [155] suggested that better knowledge could improve understanding of the organic food attributes and their benefits, and it could accelerate consumption. This could be facilitated through effective advertising that will combine both textual and visual elements in a complementary way, pointing out specific elements that can lead to a positive influence on how individuals perceive organic food overall [151,157].…”
Section: Conclusion-implementationmentioning
confidence: 99%